2022
DOI: 10.1021/acs.langmuir.1c03364
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Assessment of Water Sorbent Kinetics

Abstract: The kinetics of water adsorption in powder sorbent layers are important to design a scaled-up atmospheric water capture device. Herein, the adsorption kinetics of three sorbents, a chromium (Cr)-based metal–organic framework (Cr-MIL-101), a carbon-based material (nanoporous sponges/NPS), and silica gel, have been tested experimentally, using powder layers ranging from ∼0 to 7.5 mm in thickness, in a custom-made calibrated environmental chamber cycling from 5 to 95% RH at 30 °C. A mass and energy transfer model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Specifically, we simulated the dynamic sorption behavior of the sorbent based on the Fickian diffusion (FD) model [ 52 ] (Note S2, Supporting Information). The FD model shows a satisfactory agreement between the theoretical and experimental data derived from both milligram‐scale samples (Figure S30, Supporting Information) and bulk samples with a specific weight of 0.45 g cm −1 (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we simulated the dynamic sorption behavior of the sorbent based on the Fickian diffusion (FD) model [ 52 ] (Note S2, Supporting Information). The FD model shows a satisfactory agreement between the theoretical and experimental data derived from both milligram‐scale samples (Figure S30, Supporting Information) and bulk samples with a specific weight of 0.45 g cm −1 (Figure 4c).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, Figure 9B showed that the reduced particle size results in faster adsorption rate. On one hand, the reduced particle size can promote the internal diffusion process 69–71 . On the other hand, the smaller particle size enlarges the external surface area (the external surface area of UiO‐66‐70 nm, UiO‐66‐162 nm, and UiO‐66‐2.5 μm are 178, 112, and 60 m 2 g −1 , respectively) and allows more adsorption sites to be exposed on the surface, 40,71,72 which can facilitate the adsorption of water molecules.…”
Section: Resultsmentioning
confidence: 99%
“…On one hand, the reduced particle size can promote the internal diffusion process. [69][70][71] On the other hand, the smaller particle size enlarges the external surface area (the external surface area of UiO-66-70 nm, UiO-66-162 nm, and UiO-66-2.5 μm are 178, 112, and 60 m 2 g À1 , respectively) and allows more adsorption sites to be exposed on the surface, 40,71,72 which can facilitate the adsorption of water molecules. At the same time, we found that the maximum water adsorption capacity was determined by the total pore volume, and the smaller the particle size, the larger the total pore volume (Figure 9C and Table 1).…”
Section: Water Adsorption Properties Of Uio-66 With Different Particl...mentioning
confidence: 99%
“…In this case, the intergranular space is filled by nearly stationary air, which increases the overall thermal resistance of a material. [63,76] During the desorption process, the captured water is desorbed into water vapor and ejected into the ambient. The existence of air thermal resistance degrades sorbent's thermal conductivity, further disturbing uniform desorption temperature.…”
Section: Influence Of Thermal Conductivitymentioning
confidence: 99%